Culturally and linguistically diverse nursing student education: a grounded theory study - Brown, Vickey Michelle (Curtin University, 2005)
This study set out to examine and describe the experiences of undergraduate students from different cultural backgrounds studying nursing across three Australian states. The researcher chose to use the grounded theory method to analyse data collected from 40 undergraduate student nurses and 32 nurse teachers. Other data resources included field observations of student nurses in clinical practice and classroom settings. All interviews were transcribed verbatim and along with field notes and memos were analysed using the constant comparative method synonymous with grounded theory. This study was set in a sociopolitical climate of disharmony in which the basic social problem of sociocultural discord: being different and not fitting in (SD) was identified and developed as the core category. The basic social psychological problem existed for culturally and linguistically diverse nursing students because they were in some way different to the majority of their White western counterparts. Differences existed in, for example, religion, dress, skin colour, beliefs, behaviours, and ways of communicating. Because these students were different they experienced discord. Discord was characterised as sociocultural because differences causing discord were rooted in either a cultural or social domain or both. Those students who experienced SD lived with feelings of social and professional isolation, discrimination, and low self esteem to name a few. For the students, experiences of sociocultural discord were largely unpredictable and occurred episodically. The fear of embarrassment, discrimination, or some other form of inequitable treatment prevented students participating actively in classes or on clinical practice.Students, however, were unable to determine when they were likely to experience inequitable treatment and for many when it had been identified it was too late; they were amidst the experience. Others were hesitant to interact with their Australian counterparts for fear of rejection. This study occurred during a particularly disharmonic climate which permeated all aspects of the students’ lives and had the propensity to impact upon individual levels of SD. As such this climate existed as the background in this study. One of the background issues identified as impacting upon students in this study was stereotyping. In this study stereotyping was often based upon perceived cultural, religious, and/or gender norms. The physical environments, that is, university campuses and clinical practice settings in which the students were required to participate, were also found to impact upon student participants and were therefore also considered as background. In these institutions there was an obvious lack of cultural role models and students’ behaviours were often misinterpreted. Whilst some students’ families were considered as immensely supportive others were identified as being the cause of much sociocultural discord. The politics of race and culture also acted to permeate the students’ existence and these issues were given wide media coverage at the time of this research. In an effort to deal with, or counter, episodes of sociocultural discord student participants engaged the process of seeking concord to get in the right track (SC). Some of these strategies worked to reduce SD whilst others did not. These strategies consisted of saving face, covert deception, and using the “yes syndrome”.Other strategies included clustering, trying to form friendships, and trying to interact with members of the dominant group. Many students struggled to suppress their feeling of SD by being quiet and/or ignoring differential treatment and avoiding interaction with others. Some adopted other strategies to strengthen their communication abilities in an effort to reduce discordant episodes. Many of these strategies were learnt from other students or supportive nurse teachers. Other support was attained from student counselling services and supportive family members. These were considered the influencing conditions. Unlike many grounded theories this study was unable to identify the end of the process, that is, successful outcomes. Irrespective that students implemented strategies to decrease their discord they continued to experience other discordant events throughout their undergraduate degree program. Whilst many of the findings in this research support the existing literature, this study can be considered as one of the first attempts to study student nurses from different cultural backgrounds and their experiences of nursing education in Australian universities.